2016
DOI: 10.18632/oncotarget.13739
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor activates inflammatory responses of astrocytes through interaction with CD74 receptor

Abstract: Astrocytes, the major glial cell population of the central nervous system (CNS), play important physiological roles related to CNS homeostasis. Growing evidence demonstrates that astrocytes trigger innate immune responses under challenge of a variety of proinflammatory cytokines. Macrophage migration inhibitory factor (MIF), a proinflammatory cytokine mainly secreted from monocytes/macrophages, is involved in inflammation-associated pathophysiology. Here, we displayed that expression of MIF significantly incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 45 publications
4
42
0
Order By: Relevance
“…Many questions remain as to how microglia and astrocytes interact with each other to influence neuronal survival during cytotoxic events (71)(72)(73)(74). While our evidence here suggests minocycline inhibited microglial activation (but not astrocyte activation) and reduced cell death, the specific contributions of individual cell types to pro-and anti-inflammatory gene expression are not completely clear.…”
Section: Discussionmentioning
confidence: 62%
“…Many questions remain as to how microglia and astrocytes interact with each other to influence neuronal survival during cytotoxic events (71)(72)(73)(74). While our evidence here suggests minocycline inhibited microglial activation (but not astrocyte activation) and reduced cell death, the specific contributions of individual cell types to pro-and anti-inflammatory gene expression are not completely clear.…”
Section: Discussionmentioning
confidence: 62%
“…In this study, we demonstrate for the first time, that MIF alters baseline functional properties of hippocampal CA1 pyramidal neurons (Figure 1), and changes the kinetics of pharmacologicallyevoked NMDA responses in the apical dendrites of these neurons (Figure 3). MIF is known to be involved in several inflammatory and trophic responses, via its role in modulating signaling mechanisms that are regulated by TLR4, p53 and CD74 signaling [11,[28][29][30][31][32][33][34][35][36][37][38][39][40]. While there is evidence showing the involvement of MIF in inflammatory pathways, as well as evidence for MIF effects on…”
Section: Discussionmentioning
confidence: 99%
“…Some of the functions of MIF in the immune system and brain have been previously explored. In an innate immune response, MIF binds to the CD74 receptor complex, along with co-stimulatory factor CD44, initiating downstream signaling cascades and facilitating the immune response [11,[28][29][30][31][32][33][34][35][36][37][38][39][40]. The MIF/CD74 signaling complex is also conserved in microglia and astrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Su et al (25) found that PLA2G2A was involved in the astrocyte-mediated inflammatory response through a transcriptome study, indicating that PLA2G2A may be functionally associated with central nervous system homeostasis. Notably, it has been well documented that RBM3 serves a critical role in the neuroprotective effect of synaptic loss (4).…”
Section: Discussionmentioning
confidence: 99%